Experimental Investigation on the Performance of a CI Engine Fueled with Waste Cooking Oil Biodiesel Blends - Devkota, Lochan Kendra; Adhikari, Surya Prasad (Himalayan Journal of Applied Science and Engineering, 2021)
In this study, different performance parameters of a Compression Ignition (CI) engine fueled with waste cooking oil biodiesel blends with diesel in different percentage volumes of 5 % biodiesel and 95 % diesel (W5), 10 % biodiesel and 90 % diesel (W10), 15 % biodiesel and 85 % diesel (W15) and 20 % biodiesel and 80 % diesel (W20) were tested experimentally. First, biodiesel was produced from waste cooking oil by transesterification process. The physical-chemical properties of biodiesel and W20 were tested. The tested properties of W20 were found to American Society for Testing and Materials (ASTM) standards near to diesel fuel. Subsequently, test of diesel and biodiesel blended fuels were carried out using 15:1 compression ratio on Kirloskar Single Cylinder Compression Ignition Engine at 1500 rpm on varying loads. The engine performance parameters for biodiesel blends such as Indicated Power (IP), Brake Power (BP), Brake Mean Effective Pressure (BMEP), Brake Thermal Efficiency (BTE), Specific Fuel Consumption (SFC) and Mechanical Efficiency (ME) against load in comparison to diesel fuel were obtained and verified those with diesel fuel. IP for diesel, W5, W10, W15 and W20 at load of 12 kg are 4.3 kW, 4.8 kW, 4.7 kW, 4.75 kW and 4.2 kW respectively. ME of W20 at 12 kg load is less by 4.1 % than diesel. The difference in SFC of diesel and W20 at 12 kg load was 0.27 kg/kWh. The experimental outcomes confirm that the IP and SFC of blended biodiesel were slightly superior. Correspondingly, BP and BMEP were also found comparable to diesel fuel.